Fibonacci Numbers as a Natural Phenomenon - Senad Orhani (International Journal of Scientific Research and Innovative Studies, 2022)
This paper presents an attempt to explain and experiment with Fibonacci numbers. It is illustrated with examples and concrete cases many of the properties of these numbers which are often found in practice or even are things that we see and touch every day. My goal has been to make a summary of writings, analyzes, studies, games, natural events as well as research by means of examples for famous Fibonacci numbers. The Fibonacci sequence can be observed in a variety of stunning phenomena in nature. Therefore, this study first presents the Fibonacci sequence and also describes some of the Fibonacci sequence phenomena presented in our living world.